Influence of Reduced Air Pollution Source Emission Information on User Behavioural Intention Towards E-Scooter Products - Huang, Fei-Hui (Promet - Traffic&Transportation, 2022)
In this study, a mobile application-based service providing information on the reduction in the air pollution source emissions due to the replacement of conventional scooters by electric scooters (e-scooters) was proposed to increase user awareness of air quality and purchase intention towards e-scooters. The extended unified theory of acceptance and use of technology was employed and an explanatory variable of environmental awareness (EA) was incorporated for enhancing constructs to investigate the factors that may influence the user acceptance of text-based mobile information on the reduced carbon emissions, in comparison with that of histogram-based mobile information on the reduction in emissions of six air pollution sources. A within-subjects experimental design was employed to evaluate both information contents. The results indicate that the model constructs of habit and EA are useful predictors of the behavioural intention (BI) to use app services. Furthermore, providing different mobile information contents demonstrated no statistically significant difference in the user’s acceptance and intentions. However, providing different mobile information contents on the same information spindle may trigger different constructs and intensities of influence on users’ purchase intentions for e-scooters. Based on these findings, several recommendations for app managers and developers and suggestions for future research have been provided.